Comparative study between effectiveness of proximal femoral nail and dynamic condylar screw in fixation of subtrochanteric femur fracture - Sarkar, Pranjal; Sourav Mal; Rakshit, Susanta; Indrajit Saha; Bandyopadhyay, Ranadeb; Saha, Debasish (Asian Journal of Medical Sciences, 2023)
Background: Subtrochanteric femur accounts for 10–30% of peri-trochanteric fractures. They need early fixation to avoid complications of prolonged immobilization. Proximal femoral nail (PFN) and dynamic condylar screw (DCS) fixation are most commonly used for subtrochanteric fracture fixation. Aims and Objectives: The purpose of the study was to evaluate the outcomes of PFN and DCS fixation of the subtrochanteric fracture. Materials and Methods: This descriptive follow-up study was conducted in Bankura Sammilani Medical College, Department of Orthopedics from May 2020 to October 2021. A simple random sampling technique with an estimated sample size of 40 patients in PFN group and 40 patients in DCS group was taken. Results: Among the PFN cases, 24 (60%) cases were reduced by closed reduction, and 16 (40%) cases were reduced by open reduction. Among DCS cases, 30 (75%) were reduced by open reduction. The average operating time in PFN patients was 80 min and in DCS patients was 104 min. The average blood loss in PFN patients was 178 mL and for DCS patients 252 mL. The average union time of PFN cases was 15.56 weeks and DCS group was 18 weeks. Out of 40 cases of PFN, there were 24 excellent, 8 good, 6 fair, and 2 poor functional outcome by Harris hip Score, and DCS fixation had 6 excellent, 16 good, 12 fair, and 6 poor functional outcome. Conclusion: There are no major differences in union rate and complication rate between the PFN and DCS. Although PFN has advantages over DCS in terms of decreased blood loss, decreased operative time, faster union, and a greater chance to closed reduction. Overall, it gives better functional result than DCS.